TikTok fitspiration and fitness ideal internalisation: gender differences in self-esteem and body satisfaction - Limniou, Maria; Duckett, Holly; Mitchell, Eleanor (Frontiers in Psychology, 2025)
IntroductionFitspiration content promotes active, healthy lifestyles by advocating for healthy eating, regular exercise, and self-care. While Instagram’s impact on body image has been widely studied, limited research has explored TikTok fitspiration. This study examined how TikTok usage influences fit ideal internalisation, state self-esteem and perceptions of physical appearance, as well as gender differences in responses to fitspiration content on body satisfaction.MethodsA total of 274 participants (61.7% females; aged 18–62, M = 21.8, SD = 7.64) completed an online questionnaire assessing TikTok usage, fit internalisation and appearance-related perceptions. Participants then viewed three fitspiration videos, and their levels of body satisfaction and state self-esteem were measured before and after exposure.ResultsPaired-samples t-tests revealed a significant decrease in body satisfaction post-exposure (p < 0.01, Cohen’s d = 0.47), while state self-esteem remained unchanged (p = 0.354, Cohen’s d = 0.023). A multivariate analysis of variance (MANOVA) showed that females’ state self-esteem and body satisfaction were significantly lower than males due to TikTok fitspiration content (p < 0.05). Multiple regression analyses revealed that among usage variables (e.g., frequency of use, posting habits, follower count), only the number of followees (β = 0.871, p = 0.020) and received “likes” (β = 1.449, p < 0.001) positively predicted fit internalisation, with no significant effect on appearance.DiscussionThese findings highlighted the importance of educational interventions to counter the influence of TikTok fitspiration content. A potential implication of this study is the promotion of a shift from aesthetic ideals to physical capabilities.